Manifested behaviors, views, and interpretations of 5 to 6 year old children on their severe typhoon experience - Maclid, Erickson M.; Reyes, Clarissa Fausto; Rodriguez, Rona Mae C. (Quezon City College of Home Economics, University of the Philippines, 2014)
Abstract This research described the manifested behaviors, views and interpretations of 5- to 6- year old children on their Severe Typhoon Experience (STE). A total of 24 purposively selected pairs of children and their significant adults from Barangay Tumana, Marikina City, participated in the qualitative study. Data were gathered through checklists, interviews and projective drawings. Respondents were categorized into four groups depending on the severity of their typhoon experience. Gathered data were analysed according to themes that emerged from the responses. Most of the children shared the same manifested behaviors after the typhoon as reported by their significant adults. The two most observed behaviors among all the children were being scared of strong winds and rain, and difficulty separating from parents. The respondents? views about their STE have minimal differences. Most children remembered events which they experienced through their senses like having strong rains and flooding. They also verbalized their feelings on help received during their STE. Majority of the children said that they are ready when the disaster happens again, However, a few also mentioned that they are not yet ready for it. The projective drawings of the children mostly shared the same elements; "bahay", "tao", and "baha" or things that they saw in abundance during their STE. These drawings served as supplements to what they were not able to verbalize. The gathered data highlighted the need for an improved disaster risk reduction system and better post disaster procedures such as debriefing of children.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Children -- Conduct of life; Life change events -- Philippines